Where the conflict really lies: science, religion, and naturalism - Plantinga, Alvin (Oxford University Press, 2011)
In this long-awaited book, pre-eminent analytical philosopher Alvin Plantinga argues that the conflict between science and theistic religion is actually superficial, and that at a deeper level they are in concord.